2020
DOI: 10.1029/2020gl089051
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Evolution of Mercury Over the Past ∼4.2 Ga as Revealed by Relaxation States of Mantle Plugs Beneath Impact Basins

Abstract: We investigated the relaxation states of 11 large impact basins on Mercury based on an updated crustal thickness map, finding that the pre-Tolstojan basins have comparable instead of varied relaxation states, suggesting that Moho temperature (Temp Moho) did not decrease substantially from ∼4.2 to 3.8 Ga. At the same time, mantle uplift beneath the Caloris basin is the least degraded, therefore implying a sharp decrease of Temp Moho ∼ 3.8 Ga. These findings contrast with our thermal evolution models that predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…Padovan et al (2017) demonstrated that post-impact residual heating of the Caloris produces significant thermal anomaly in Mercury's mantle and changes the source depth of magma. Deng et al (2020) investigated the relaxation state of large impact basins on Mercury, suggesting that impact bombardment prior to the formation of the Caloris basin inputted substantial energy to the interior. Wang et al (2021) noticed that smooth plains on Mercury were formed in a relatively small time window between ∼3.5 and 3.7 Ga, and the plains are preferentially distributed around several coeval large impact basins, suggesting that large impact basins may be an important trigger of the last episode of global volcanism on Mercury (Large impact basins are preferential locations for volcanism because of the crustal thinning, crustal porosity generation, and low-lying topography).…”
mentioning
confidence: 99%
“…Padovan et al (2017) demonstrated that post-impact residual heating of the Caloris produces significant thermal anomaly in Mercury's mantle and changes the source depth of magma. Deng et al (2020) investigated the relaxation state of large impact basins on Mercury, suggesting that impact bombardment prior to the formation of the Caloris basin inputted substantial energy to the interior. Wang et al (2021) noticed that smooth plains on Mercury were formed in a relatively small time window between ∼3.5 and 3.7 Ga, and the plains are preferentially distributed around several coeval large impact basins, suggesting that large impact basins may be an important trigger of the last episode of global volcanism on Mercury (Large impact basins are preferential locations for volcanism because of the crustal thinning, crustal porosity generation, and low-lying topography).…”
mentioning
confidence: 99%
“…In addition, ∼20% of small volcanic smooth plains are associated with crustal thicknesses larger than >40 km, although they are also located in regionally low topography areas (Figure 4d). If smooth volcanic plains were mostly contained with impact structures, the distribution of irregularly shaped small smooth plains (Figures 4c and 4d) indicates that earlier crust of Mercury has been strongly deformed (Orgel et al., 2020), so topographic and geophysical evidence of ancient basins is no longer visible (Deng et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A sharp decline in volcanic activity at ∼3.6 Ga is consistent with the thermal history of Mercury. The Moho uplift formed by the Caloris basin was much less affected by viscous relaxation compared with those formed by older basins, as older ones exhibit similar relaxation states regardless of their stratigraphic ages (Deng et al., 2020). Before the Caloris impact, intense impact bombardment might have added external heat to the interior of Mercury (Padovan et al., 2017), slowing down interior cooling (Roberts & Barnouin, 2012) and promoting the relaxation of mantle plugs beneath basins older than Caloris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we have achieved favorable fitting results by employing a mantle and mare basalt load model, which effectively constrains the lithospheric structure parameters in mare basins (Figures 9, 10, 12, panels (d) and (e)). In contrast, traditional load models have proven inadequate in accurately fitting the theoretical and observational spectra (Deng, Xiao, et al., 2023; Deng, Zhong, et al., 2023; Zhong et al., 2022). Hence, this approach offers a potential solution for future research on determining the structural parameters of the lithosphere in a broader range of mascon basins on the Moon.…”
Section: Discussionmentioning
confidence: 99%